Use of Distillers Dried Grains with Solubles (DDGS) as Replacement for Soybean Meal in Laying Hen Diets - Ghazalah, A.A.; Abd-Elsamee, M.O.; Moustafa, Eman S. (International Journal of Poultry Science, 2011)
An experiment was conduced to evaluate the inclusion of Distillers Dried Grains with Solubles (DDGS) in commercial layer diets with Avizyme 1500® supplementation. Two hundred eighty-eight 40-week-old Bovans brown layers were distributed in a completely randomized experimental design in a 2 x 4 factorial arrangement, with the variables being (DDGS) substitution for soybean meal at four levels (0 or 25% or 50% or 75%) and Avizyme 1500 at two levels (0 or 0.075%). Layer performance, egg quality, nutrients digestibility and blood parameters were evaluated. Results showed that average egg production, egg weight, egg mass, feed conversion ratio and the change in body weight of laying hens were significantly (p